Signal Transduction in the Cardiovascular System in Health and Disease - Srivastava, Ashok K. (Springer, 2017)
This book has addressed the contributions of several key signal transduction pathways which are central to our understanding of cardiovascular physiology and pathophysiology. Aberrations in these signaling events have been suggested to be involved in a host of cardiovascular pathologies, such as cardiac arrhythmias, congenital heart failure and hypertension.